The Great Betrayal: Potential Statelessness After Living Decades In Mother India - Subrata Sankar Bagchi (Institut Hindu Dharma Negeri Denpasar, 2017)
An amendment in the Indian Citizenship Act (2005) may render millions of citizens stateless with the new clause of “illegal migrant” without any cut-off date, as most of the immigrants particularly from Eastern Bengal, came to India facing persecution and without any legal document of immigration.